ARCEDEM - design and manufacture in agricultural engineering - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The African Regional Centre for Engineering Design and Manufacture (ARCEDEM) came into existence in 1980 in response to the urgent need for Africa to feed its population effectively. Those who established the Centre believed that increases in...